Factors associated with disease in farmed and wild salmonids caused by Tenacibaculum maritimum: a scoping review - Wassmuth, Rebecca M.; de Jongh, Etienne J.; Uhland, F. Carl; Reid-Smith, Richard J.; Robertson, Kelsey; Otto, Simon J. G. (Frontiers in Aquaculture, 2024)
IntroductionYellow mouth disease, caused by Tenacibaculum maritimum, is an important disease of farmed salmonids. Disease management currently necessitates the use of antimicrobials, raising concerns about antimicrobial resistance (AMR) in aquatic and potentially terrestrial environments. Identifying management, production, environmental, and other factors associated with the development of yellow mouth in salmonids will help to elucidate disease control strategies and decrease the economic and environmental burden of its treatment. The objective of this scoping review was to synthesize the available literature to identify factors associated with disease in farmed and wild salmonids from T. maritimum.MethodsThe scoping review followed the framework outlined in the Joanna Briggs Institute Reviewer’s Manual and PRSIMA-ScR reporting guidelines. The protocol was developed a priori in consultation with a librarian and was used to search Environment Complete®, Earth, Atmospheric, and Aquatic Science®, Scopus®, and Web of Science™ databases on July 21, 2022, and again on April 27, 2023. Articles were included if they focused on T. maritimum infection in salmonids and discussed factors (environmental, management, or other) that impacted the disease and/or organism of interest.ResultsTwenty-five articles were included for review. Over half were published within the last five years (n=14/25). The included articles revealed a complex interplay of salmonid (host)-specific factors (age/size), management practices (vaccination, marine transfer, stocking density, gill/body abrasion), environmental conditions (water temperature, oxygenation, salinity, algal blooms, vectors), and microbial dynamics (load, co-infections, strain, biofilms, microbiome) influencing T. maritimum infections. Only one study conducted multivariable analysis to understand this complex interplay between the diverse factors that impact infection with T. maritimum.DiscussionThe review highlights the complex, multifactorial nature of T. maritimum infections, including the interplay of host biology, environmental factors, and pathogen characteristics. A comprehensive approach incorporating both management and environmental components is essential to mitigate T. maritimum infections in salmonid production.